Study the effect of a new nikel (II) Complex and anticancer drug (cp) on Liver enzyme activity (GPT,GOT) and Creatinine level in Kidney of femal mice (Baghdad Science Journal, 2014)
This study involved the effect of anew nickel (II) complexs with formla [NiL2(H2O)2].2.5ETOH where L=Bis[5-(p-nitrophenyL)-4-phenyL-1,2,4-traizole-3-dithocarbamato hydrazide] diaqua. nickel(II). Ethanol(2.5).and anti-cancer drug cyclophosphamide on specific actifity of two Liver enzymes (GOT,GPT) in the (Liver,kidney) tissues and on the creatinine Level in the kidney byUtilizing an invivosystem in femalmice.The result showed that inhibition in the activity of GPT and GOT enzymes in theLiver and in both nickel (II) complex and cyclophosphamide drug (CP) . mice weretreated with three doses (90,180,320) µg/mouse for three days for each group.The Liver show's the highest rate of GPT inhibition was about 97.43% at180µg/mouse regarding the kidney the inhibition rate was about 98.63% at 180µg/mouse .The maximum inhibition of GOT enzame in the Liver was about 77. 48% ataconcentration 180µg/mouse and the inhbition rate of GOT enzyme in the kidney was about 97.87% at aconcentration 320µg/mouse.The result showed the effect of nickel (II) complex on the creatinine Level in the kidney ,The maximum activation was about 99.45% at 320µg/mouse.